The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/cphc.200600353
|View full text |Cite
|
Sign up to set email alerts
|

Organic Molecular Beam Deposition of Oligophenyls on Au(111): A Study by X‐ray Absorption Spectroscopy

Abstract: Near-edge X-ray absorption fine structure (NEXAFS) spectroscopy has been applied to reveal the molecular arrangement of ultrathin oligophenyl films [p-quaterphenyl (4P) and p-hexaphenyl (6P)] on Au(111). In the half-monolayer films the molecules lie flat on the surface but still have a considerable inter-ring twist of 30 degrees -40 degrees , similar to the gas-phase conformation. In the saturated monolayer film the second half of the molecules is side-tilted by an angle of less than 66 degrees with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…This conclusion is consistent with the planar adsorption geometry of p-hexaphenyl on Au(111). 35 Note that the unoccupied frontier orbitals simulated using extended Hückel theory after geometry optimization of (M,M)-2 on a single Cu(100) layer ( Fig. 2d) agree very well with the observed STM contrast, thereby confirming the assignment of the sense of helicity of the two helical subunits.…”
supporting
confidence: 72%
“…This conclusion is consistent with the planar adsorption geometry of p-hexaphenyl on Au(111). 35 Note that the unoccupied frontier orbitals simulated using extended Hückel theory after geometry optimization of (M,M)-2 on a single Cu(100) layer ( Fig. 2d) agree very well with the observed STM contrast, thereby confirming the assignment of the sense of helicity of the two helical subunits.…”
supporting
confidence: 72%
“…Furthermore, Müllegger et al measured OMBE grown thin fi lms of quaterphenyl and found a significantly less pronounced dichroism compared to our case. [ 16 ] The authors showed that such a weak angle-dependence is consistent with the typical herringbone packing of oligophenyl molecules.…”
Section: Wileyonlinelibrarycommentioning
confidence: 70%
“…[8] On clean gold the first organic layer consists of flat lying molecules and lying molecules which have their molecular planes tilted by 668 with respect to the substrate. [9] In contrast, on the carbon precovered substrate the molecular plane tilt is constant in the monolayer, but their relative in-plane orientation is randomly distributed due to the lack of order in the graphitic layer. An other approach is to deposit molecules with functional groups (i.e.…”
Section: Introductionmentioning
confidence: 94%